2010
DOI: 10.1080/00224499.2010.494776
|View full text |Cite
|
Sign up to set email alerts
|

“You Still Need to Give Her a Token of Appreciation”: The Meaning of the Exchange of Money in the Sexual Relationships of Out-of-School Adolescents in Rural Southwest Uganda

Abstract: This article challenges the pervasive assumption that exchanging gifts and money in adolescent sexual relationships is transactional. Data were derived from a multi-method, qualitative sexual health needs assessment of 31 out-of-school adolescents in rural southwest Uganda. Grounded theory analysis allows contextual meanings of exchange to emerge. Adolescents have developed gendered courting and exchange models that parallel marital relationships in this cultural context. Whereas exchange is considered transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Our observations are in agreement with a similar study in Uganda (Nobelius et al, 2010) where the presentation or acceptance of goods or gifts was associated with transactional sex (Hingson et al, 2003;Wamoyi et al, 2010). Unplanned sex may also serve to escape certain situations, illustrating the interaction between personal and environmental factors on students' behaviours.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are in agreement with a similar study in Uganda (Nobelius et al, 2010) where the presentation or acceptance of goods or gifts was associated with transactional sex (Hingson et al, 2003;Wamoyi et al, 2010). Unplanned sex may also serve to escape certain situations, illustrating the interaction between personal and environmental factors on students' behaviours.…”
Section: Discussionsupporting
confidence: 92%
“…Focus group discussions in Uganda revealed that rural out-ofschool young women find material need a more appropriate motive for sex than pleasure (Nobelius et al 2010b). In quantitative research among 628 out-of-school youth aged between 15 and 24 in Bahir town, Alemu et al (2007) observed that the probability of having sex with either a commercial or a non-regular sexual partner rose with a factor ranging between 1.83 and 4.23 (CI 95%) for out-ofschool adolescents who drink alcohol at least once a week (in comparison to out-of-school youth reporting no alcohol intake).…”
Section: Methodsmentioning
confidence: 99%
“…This is because these young women engage in transactional sex not willingly but because of economic reasons. Studies have reported high HIV prevalence and incidence rates among uneducated and unemployed young women who live in poverty in rural parts of SSA (Barnett & Maticka-Tyndale, 2011;Nobelius et al, 2010).…”
Section: Socioeconomic Factorsmentioning
confidence: 99%